Entrepreneurial business: genetic lottery or a choice - Nikolić, Slavka; Kovijanić, Tijana; Mladenović, Marijana; Ćelić, Đorđe (Journal of Business Economics and Management, 2020)
Research dedicated to entrepreneurship has, from the very beginning, created a gender gap as it was mostly considered to be the masculine one. Studies with the main focus on psychological characteristics of entrepreneurs are mostly based on a comparison with other professionals, rarely approaching gender differences. Using the mixture of general personal and entrepreneurial traits, this study investigates entrepreneurial dilemma and answers the question whether entrepreneurship can or cannot be gendered, using a sample of potential entrepreneurs. Based on the multivariate analysis of variance, this study empirically proves that there are no statistically significant differences between the genders according to any criteria, except for the criterion of worry, which is more pronounced in women than in men. This study offers a good basis for the implementation of the existing models in different areas of entrepreneurship research, extending its understanding from the gender perspective. From the practical point of view, it provides a deeper understanding of entrepreneurial traits that might be critical for designing support and educational programs for enhancing (female) entrepreneurship.